Microstructural evolution and refinement of as-forged Ti–43Al–9V–Y alloy after quenching and tempering. (October 2019) - Chen, Lin; Lin, Junpin; Xu, Xiangjun; Chen, Yuyong; Kong, Fantao; Liang, Yongfeng
Abstract: It is shown that a uniform and refined fully lamellar microstructure can be generated by tempering the quenched samples in the single α region of as-forged Ti–43Al–9V–Y alloy. The refining effect was mainly connected with the quenched microstructures especially for their substructure, grain size and the residual β particles after the quenching. A series of β-decomposed products: martensite plate, massive α and coarsened α lath with increasing grain size were produced due to the decreasing cooling rate during the wedge-shaped sample quenched into iced brine. In addition, the decomposition of β directly to γ has also been observed during the quenching with different cooling rate. The lamellar colony size can be controlled in the range of 25–50 μm after tempering. Highlights: Uniform and refined fully lamellar structure can be obtained by quenching and tempering. The β-decomposed product varies from martensitic α plate, massive α to coarsened α lath with decreasing quenching rate. The lamellar colony size after tempering is mainly connected with the quenched microstructures.